Necessary and sufficient conditions for oscillation of solutions of nonlinear pulse systems with multiplicatively separated right-hand side - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Necessary and sufficient conditions for oscillation of solutions of nonlinear differential equations with fixed times of pulse influence and multiplicatively separated right-hand sides are established.